Evaluation of dispersion type metal···π arene interaction in arylbismuth compounds – an experimental and theoretical study - Preda, Ana-Maria; Krasowska, Małgorzata; Wrobel, Lydia; Kitschke, Philipp; Andrews, Phil C.; MacLellan, Jonathan G.; Mertens, Lutz; Korb, Marcus; Rüffer, Tobias; Lang, Heinrich; Auer, Alexander A.; Mehring, Michael (Beilstein Journal of Organic Chemistry, 2018)
The dispersion type Bi···π arene interaction is one of the important structural features in the assembly process of arylbismuth compounds. Several triarylbismuth compounds and polymorphs are discussed and compared based on the analysis of single crystal X-ray diffraction data and computational studies. First, the crystal structures of polymorphs of Ph3Bi (1) are described emphasizing on the description of London dispersion type bismuth···π arene interactions and other van der Waals interactions in the solid state and the effect of it on polymorphism. For comparison we have chosen the substituted arylbismuth compounds (C6H4-CH═CH2-4)3Bi (2), (C6H4-OMe-4)3Bi (3), (C6H3-t-Bu2-3,5)3Bi (4) and (C6H3-t-Bu2-3,5)2BiCl (5). The structural analyses revealed that only two of them show London dispersion type bismuth···π arene interactions. One of them is the styryl derivative 2, for which two polymorphs were isolated. Polymorph 2a crystallizes in the orthorhombic space group P212121, while polymorph 2b exhibits the monoclinic space group P21/c. The general structure of 2a is similar to the monoclinic C2/c modification of Ph3Bi (1a), which leads to the formation of zig-zag Bi–arenecentroid ribbons formed as a result of bismuth···π arene interactions and π···π intermolecular contacts. In the crystal structures of the polymorph 2b as well as for 4 bismuth···π arene interactions are not observed, but both compounds revealed C–HPh···π intermolecular contacts, as likewise observed in all of the three described polymorphs of Ph3Bi. For compound 3 intermolecular contacts as a result of coordination of the methoxy group to neighboring bismuth atoms are observed overruling Bi···π arene contacts. Compound 5 shows a combination of donor acceptor Bi···Cl and Bi···π arene interactions, resulting in an intermolecular pincer-type coordination at the bismuth atom. A detailed analysis of three polymorphs of Ph3Bi (1), which were chosen as model systems, at the DFT-D level of theory supported by DLPNO-CCSD(T) calculations reveals how van der Waals interactions between different structural features balance in order to stabilize molecular arrangements present in the crystal structure. Furthermore, the computational results allow to group this class of compounds into the range of heavy main group element compounds which have been characterized as dispersion energy donors in previous work.
Keywords: arylbismuth compounds; DFT-D; dispersion type Bi···π arene interaction; DLPNO-CCSD(T); electronic structure calculations; polymorphism; single crystal X-ray structure

(untitled) - Auer, A. A.; Mansfeld, D.; Nolde, C.; Schneider, W.; Schürmann, M.; Mehring, M. (Organometallics, 2009)

(untitled) - Schmidbaur, H.; Schier, A. (Organometallics, 2008)

(untitled) - Silvestru, C.; Breunig, H. J.; Althaus, H. (Chem. Rev., 1999)

(untitled) - Cangelosi, V. M.; Pitt, M. A.; Vickaryous, W. J.; Allen, C. A.; Zakharov, L. N.; Johnson, D. W. (Cryst. Growth Des., 2010)

The Importance of Pi-Interactions in Crystal Engineering - Zukerman-Schpector, J.; Tiekink, E. R. T. (Intermolecular C–H · · · π(Chelate) Interactions – Prevalence in the Crystal Structures of Metal 1,1-Dithiolates, 2012)

(untitled) - Schneider, W. B.; Bistoni, G.; Sparta, M.; Saitow, M.; Riplinger, C.; Auer, A. A.; Neese, F. (J. Chem. Theory Comput., 2016)

(untitled) - Bistoni, G.; Auer, A. A.; Neese, F. (Chem. – Eur. J., 2017)

(untitled) - Grimme, S.; Hansen, A.; Brandenburg, J. G.; Bannwarth, C. (Chem. Rev., 2016)

(untitled) - Liptrot, D. J.; Power, P. P. (Nat. Rev. Chem., 2017)

(untitled) - Caracelli, I.; Haiduc, I.; Zukerman-Schpector, J.; Tiekink, E. R. T. (Coord. Chem. Rev., 2013)

(untitled) - Caracelli, I.; Zukerman-Schpector, J.; Haiduc, I.; Tiekink, E. R. T. (CrystEngComm, 2016)

(untitled) - Tiekink, E. R. T. (Coord. Chem. Rev., 2017)

(untitled) - Sadler, P. J.; Li, H.; Sun, H. (Coord. Chem. Rev., 1999)

(untitled) - Briand, G. G.; Burford, N. (Chem. Rev., 1999)

(untitled) - Yang, N.; Sun, H. (Coord. Chem. Rev., 2007)

(untitled) - Monakhov, K. Y.; Gourlaouen, C.; Zessin, T.; Linti, G. (Inorg. Chem., 2013)

(untitled) - Fanfrlik, J.; Sedlak, R.; Pecina, A.; Rulíšek, L.; Dostál, L.; Moncóľ, J.; Růžička, A.; Hobza, P. (Dalton Trans., 2016)

(untitled) - Arora, J. S.; Gaikar, V. G. (RSC Adv., 2016)

(untitled) - Senevirathna, D. C.; Werrett, M. V.; Pai, N.; Blair, V. L.; Spiccia, L.; Andrews, P. C. (Chem. – Eur. J., 2017)

(untitled) - Srinivas, K.; Suresh, P.; Babu, C. N.; Sathyanarayana, A.; Prabusankar, G. (RSC Adv., 2015)

(untitled) - Hering-Junghans, C.; Schulz, A.; Villinger, A. (Chem. Commun., 2015)

(untitled) - Hering-Junghans, C.; Schulz, A.; Thomas, M.; Villinger, A. (Dalton Trans., 2016)

(untitled) - Schwamm, R. J.; Coles, M. P.; Fitchett, C. M. (Dalton Trans., 2017)

(untitled) - Luqman, A.; Blair, V. L.; Brammananth, R.; Crellin, P. K.; Coppel, R. L.; Kedzierski, L.; Andrews, P. C. (Eur. J. Inorg. Chem., 2015)

(untitled) - Mansfeld, D.; Mehring, M.; Schürmann, M. (Z. Anorg. Allg. Chem., 2004)

(untitled) - Toma, A. M.; Pop, A.; Silvestru, A.; Rüffer, T.; Lang, H.; Mehring, M. (Dalton Trans., 2017)

(untitled) - Breunig, H. J.; Haddad, N.; Lork, E.; Mehring, M.; Mügge, C.; Nolde, C.; Raţ, C. I.; Schürmann, M. (Organometallics, 2009)

(untitled) - Preda, A. M.; Schneider, W. B.; Rainer, M.; Rüffer, T.; Schaarschmidt, D.; Lang, H.; Mehring, M. (Dalton Trans., 2017)

(untitled) - Preda, A. M.; Schneider, W. B.; Schaarschmidt, D.; Lang, H.; Mertens, L.; Auer, A. A.; Mehring, M. (Dalton Trans., 2017)

(untitled) - Bauzá, A.; Quiñonero, D.; Deyà, P. M.; Frontera, A. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Bauzá, A.; Quiñonero, D.; Deyà, P. M.; Frontera, A. (CrystEngComm, 2013)

(untitled) - Neese, F.; Hansen, A.; Liakos, D. G. (J. Chem. Phys., 2009)

(untitled) - Neese, F.; Hansen, A.; Wennmohs, F.; Grimme, S. (Acc. Chem. Res., 2009)

(untitled) - Hansen, A.; Liakos, D. G.; Neese, F. (J. Chem. Phys., 2011)

(untitled) - Liakos, D. G.; Hansen, A.; Neese, F. (J. Chem. Theory Comput., 2011)

(untitled) - Riplinger, C.; Neese, F. (J. Chem. Phys., 2013)

(untitled) - Riplinger, C.; Sandhoefer, B.; Hansen, A.; Neese, F. (J. Chem. Phys., 2013)

(untitled) - Riplinger, C.; Pinski, P.; Becker, U.; Valeev, E. F.; Neese, F. (J. Chem. Phys., 2016)

(untitled) - Wenzel, J. (Z. Kristallogr., Kristallgeom., Kristallphys., Kristallchem., 1942)

(untitled) - Hawley, D. M.; Ferguson, G.; Harris, G. S. (Chem. Commun., 1966)

(untitled) - Hawley, D. M.; Ferguson, G. (J. Chem. Soc. A, 1968)

(untitled) - Jones, P. G.; Blaschette, A.; Henschel, D.; Weitze, A. (Z. Kristallogr., 1995)

(untitled) - Bučinský, L.; Jayatilaka, D.; Grabowsky, S. (J. Phys. Chem. A, 2016)

(untitled) - Michaelis, A.; Polis, A. (Ber. Dtsch. Chem. Ges., 1887)

(untitled) - Michaelis, A. (Justus Liebigs Ann. Chem., 1889)

(untitled) - Pfeiffer, P. (Ber. Dtsch. Chem. Ges., 1904)

Soviet Patent - Florinskij, F. S.; Koton, M. M. (Preparation of tris(p-vinylphenyl)antimony or –bismuth, 1964)

(untitled) - Supniewski, J. V.; Adams, R. (J. Am. Chem. Soc., 1926)

(untitled) - Gillmeister, A. (Ber. Dtsch. Chem. Ges., 1897)

(untitled) - Hassan, A.; Breeze, S. R.; Courtenay, S.; Deslippe, C.; Wang, S. (Organometallics, 1996)

(untitled) - Petiot, P.; Dansereau, J.; Gagnon, A. (RSC Adv., 2014)

(untitled) - Grimme, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Martinez, C. R.; Iverson, B. L. (Chem. Sci., 2012)

(untitled) - Ogawa, T.; Ikegami, T.; Hikasa, T.; Ono, N.; Suzuki, H. (J. Chem. Soc., Perkin Trans. 1, 1994)

(untitled) - Stavila, V.; Thurston, J. H.; Prieto-Centurión, D.; Whitmire, K. H. (Organometallics, 2007)

(untitled) - Nishio, M. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Nishio, M. (CrystEngComm, 2004)

(untitled) - Alvarez, S. (Dalton Trans., 2013)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

(untitled) - Mantina, M.; Chamberlin, A. C.; Valero, R.; Cramer, C. J.; Truhlar, D. G. (J. Phys. Chem. A, 2009)

(untitled) - Haack, R.; Schulz, S.; Jansen, G. (J. Comput. Chem., 2018)

(untitled) - Hébert, M.; Petiot, P.; Benoit, E.; Dansereau, J.; Ahmad, T.; Le Roch, A.; Ottenwaelder, X.; Gagnon, A. (J. Org. Chem., 2016)

(untitled) - Rao, M. L. N.; Dhanorkar, R. J. (RSC Adv., 2016)

(untitled) - Neese, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2012)

(untitled) - Krasowska, M.; Schneider, W. B.; Mehring, M.; Auer, A. A. (Chem. – Eur. J., 2018)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

SHELXL-2013, Program for Crystal Structures Refinement (University of Göttingen, 2013)

SHELXL-2014, Program for the Solution of Crystal Structures (University of Göttingen, 2014)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

DIAMOND Visual Crystal Structure Information System, 31d (Crystal Impact, 2006)